Do the materials matter? A review of the literature and analysis of the materials properties of urethral stents for hypospadias repair. Issue 2 (April 2022) - Rowe, Courtney K.; Jamdee, Tawan; Foster, Christopher; Burke, Kelly A.
Summary: Introduction: Despite the prevalence of hypospadias surgery and the common use of postoperative urethral stents, there has been no evaluation of the material properties of common stents. Our study sets out to close this gap with a literature review of recent publications comparing outcomes after hypospadias surgery for different urethral stent types and an evaluation of the material properties of four common urethral stents. Study design: A review of the English language literature from 2011 to 2021 was performed. Thermal analysis and mechanical analysis of the Zaontz Urethral Stent, the Firlit-Kluge Urethral Stent, the Koyle Diaper Stent, and the Bard Premature Infant Feeding Tube was also undertaken. Results: Out of 165 papers, four met inclusion criteria. There was limited research on this topic, and no significant evidence that different stent materials impacted surgical complication rates. One study found improved comfort with the Zaontz stent, and another found a reduction emergency room visits with the Koyle stent. Using a foley balloon was associated with increased fistula rates, though this was likely due to the balloon design and not the material. Analysis of stents shows that all four are rubbery polymers at body temperature (Summary Table). The Zaontz and Koyle stents are thermoplastic elastomers with strong melting transitions above body temperature, but the Firlit-Kluge stent is amorphous at 37 °C and is likely covalently cross-linked to generate the network. The Bard feeding tube was the stiffest, with a Young's Modulus of 14.0 ± 0.78 (compared to 4.12 ± 0.56 for Zaontz, 4.92 ± 0.63 for Firlit-Kluge, and 4.09 ± 0.49 for Koyle). The Bard Feeding Tube is also the least extensible, fracturing at just over 300% strain compared to the other stents that can be stretched to greater than 2000% strain before fracture. Cyclic deformation studies demonstrate that the Zaontz, Firlit-Kluge, and Koyle stents are able to stretch and recover their shape more completely, a finding determined by the lower amount of plastic deformation those stents display compared to the Bard Feeding Tube. Discussion: While there is little information associating urethral stent type with outcomes after hypospadias surgery, material properties may account for findings of prior studies. Stiffer stents may contribute to decreased postoperative comfort, while a stent that is too soft and extensible may have issues with dislodgement, kinking and breaking. Conclusion: This study provides the foundation for future work optimizing urethral stents, designing support for regenerative medicine applications, and improving hypospadias outcomes. Summary Table Stent Manufacturer Material Est. Cost Young's Modulus Ultimate Stress (MPa) Ultimate Strain (%) Zaontz Urethral Stent Cook Medical C-Flex 28 4.12 ± 0.56 65.5 ± 2.57 2190 ± 34 Firlit-Kluge Urethral Stent Cook Medical Silicone 26 4.92 ± 0.63 84.3 ± 2.83 2125 ± 29 Koyle Diaper Stent Cook Medical C-Flex 39 4.09 ± 0.49 66.8 ± 3.16 2204 ± 41 Bard Premature Infant Feeding Tube Bard Medical Plastic 14 14.0 ± 0.78 34.6 ± 1.89 312.5 ± 16